PENINGKATAN KUALITAS PRODUK UKM IKAN ASAP PROGRAM IbM DI KOTA SEMARANG - Barokah, Siti Nur; Utami, Hadiahti -; Marsudi, Marsudi - (Politeknik Negeri Semarang, 2016)
Fish fumigation effort is one form ofeconomic activity in the village BandarharjoNorthern District of Semarang-basedhouseholds. The number of entrepreneurs inthe Center Industrial Fish Smoke inSemarang approximately 35 entrepreneursand have a considerable role in supportingthe economic movement of the people andhelp the city government's program to reduceunemployment, constraints faced by UKM inimproving competitiveness is the limitation ofthe means of production , limitations thecompany's management (finance andmarketing), yet have a fish cleaning andhygienic production space and representative,labor is not using safety equipment, becausethey have not understood the importance of K3 in the works. UKM Partner namely IkanAsap Bapak Sa'at and Ikan Asap Bapak HRustiono. Steps taken is to provide trainingand mentoring which includes the handling offinancial management, production andmarketing as well as make the chimney of abrick, tile floors production site, wherewashing fish of cement, gutter for drainage,signage, socialize K3 and provide equipmentproduction and safety equipment as acomplete work. With the training andguidance given, then the UKM Partners mayconduct financial management, calculate thecost of production and the selling price ofproducts. In addition UKM Partners canconduct production process with better,cleaner and healthier products.